Effect of intradialytic physical activity on the quality of life, biological parameters and sleep in hemodialysis patients - Gallot, Mélanie; Rieth, Nathalie; Ganea, Alexandre (Journal of Clinical Nephrology, 2019)
Many side effects, in addition to those of the pathology itself, have occurred with hemodialysis treatment but existing literature have shown that physical activity is beneficial to hemodialysis patients. Nevertheless, our parameters have not been studied enough with a resistance training program. In our study we have observed the effect of a 12-week intradialytic resistance training program (T0 vs T12) on the quality of life using the KDQOL-SF questionnaire, blood samples biological parameters and sleep using the Epworth scale and the International restless legs syndrome study group scale. The resistance training program consists of 3 sessions per week and involved lower extremities thanks to elastic band and soft ball. After the training program, the quality of life score trend to the increase at T12 compared to T0. Among the biological parameters, the only trend decrease observed was in the C-reactive protein and a trend increase was observed in urea at T12. Dialysis efficiency presented no changes and no significant results were observed for sleep. Some trends were observed as a result of our program. The type of exercise seems to have different effects on measured parameters. Nevertheless, exercise was beneficial to chronic hemodialysis patients and seemed to improve their health.